Clinical outcomes and aortic remodeling after Castor single-branched stent-graft implantation for type B aortic dissections involving left subclavian artery - Yuan, Zihui; Zhang, Lihua; Cai, Fei; Wang, Jian (Frontiers in Cardiovascular Medicine, 2024)
Background The left subclavian artery (LSA) can be intentionally covered by a stent graft to acquire adequate landing zones for a proximal entry tear near the LSA during thoracic endovascular aortic repair (TEVAR). The Castor single-branched stent graft is designed to treat type B aortic dissection (TBAD) to retain the LSA during TEVAR. This study investigates clinical outcomes, aortic remodeling, and abdominal aortic perfusion patterns after TEVAR with the novel Castor device. Methods From November 2020 to June 2023, 29 patients with TBAD involving the LSA were treated with the Castor single-branched stent graft. In-hospital clinical outcome and aortic computed tomography angiography (CTA) data were analyzed. CTA was performed preoperatively and at follow-up to observe stent morphology; branch patency; endoleak; change in true lumen (TL), false lumen (FL), and transaortic diameters; and abdominal aortic branch perfusion pattern. Results The technical success rate was 96.6%. One failure was that the branch section did not completely enter the LSA and the main body migrated distally. No in-hospital mortality, paraplegia, or stroke occurred. During follow-up, one type Ib endoleak, four distal new entry tears, and one recurrent type A dissection arose from a new entry tear at the ascending aorta, no stent migration was observed, and the branch patency rate was 100%. At the thoracic aorta, TL diameters significantly increased, FL diameters markedly decreased, and FL was partially or completely thrombosed in most patients at follow-up. At the abdominal aorta, we observed 33.3% of TL growth and 66.7% of TL stabilization or shrinkage. The initial TL ratio at iliac bifurcation negatively predicted abdominal TL growth after TEVAR with a cutoff of 21.0%. Of the 102 abdominal aortic branches, 94.1% of the branches showed no change in perfusion pattern, 3.9% of the branches had an increased TL perfusion, and 2.0% of the branches had an increased FL contribution. Conclusion The Castor unibody single-branched stent graft offers an efficient endovascular treatment for TBAD involving the LSA. TEVAR with the Castor device effectively induced thoracic FL thrombosis and thoracic TL enlargement and resulted in abdominal TL growth when the initial TL ratio at iliac bifurcation is less than 21.0%. Abdominal aortic branch perfusion patterns remain relatively stable after TEVAR with the Castor stent graft.